Analisis Kesulitan Guru Sekolah Dasar Dalam Menanamkan Pendidikan Karakter Pasca Pandemi Covid-19 - Sulastri, Dinia; Husniati; Jiwandono, Ilham Syahrul (Journal of Classroom Action Research, 2022)
The character of students in Indonesia is still relatively low. Character education is very important for students. Character education aims to form continuous individual self-improvement and train self-ability in order to lead to a better life. This study aims to describe the difficulties experienced by teachers in planning, implementing and evaluating student character values ​​after the Covid-19 pandemic at SDN 1 Peresak. The type of research used is descriptive qualitative with data collection techniques using observation, interviews and documentation. There are three data analysis techniques used, namely data condensation, data presentation and conclusion drawing, while to test the validity of the data using credibility, dependability, transferability and confirmability tests. The results of this study indicate that teachers have difficulty in preparing lesson plans such as analyzing KD to be translated into indicators, determining effective learning methods and linking learning materials with character values. Teachers also experience difficulties in implementing learning, namely instilling the values ​​of social care, tolerance, responsibility and discipline because while learning is taking place there are students who do not reflect these character values. So that the strengthening of four of the six character values ​​that became the focus of the study did not go as expected. Then the teacher also has difficulty when evaluating student attitudes that reflect the character values ​​that have been instilled by the teacher. This difficulty occurs because the teacher cannot observe student behavior when outside the classroom or during recess, making it difficult for teachers to evaluate student attitudes. Therefore, it can be concluded that SDN 1 Peresak teachers have difficulty in instilling character education, namely when planning learning that contains character values, instilling character values ​​in the implementation of learning and evaluating student attitudes that reflect character values.